Download presentation

Presentation is loading. Please wait.

Published byAlyson Lester Modified over 8 years ago

3
(x – 8) (x + 8) = 0 x – 8 = 0 x + 8 = 0 + 8 - 8 x = 8 x = - 8 10 7 52 (x + 5) (x + 2) = 0 x + 5 = 0 x + 2 = 0 - 5 - 2 x = - 5 x = - 2

4
(5x + 3) (x + 1) = 0 5x + 3 = 0 x + 1 = 0 - 3 - 1 5x = - 3 x = - 1 5315 5 31 51 3 x x 55 x = - 3 / 5 - 10- 4(2)c 2(2) (10) 2 - 4(2)(4)

5
- 10 2(2) (10) 2 - 4(2)(4) - 10 4 100- 32 - 10 4 68 2 34 2 17 - 10 4 2 17 √ ± x = √ ± √ ± - 5- 5 2 1 √ -5-5 2 17 x = ±

6
+ 8 x 2 + 6x = 8 (x + 3) 2 = 17 + 9 +3x x2x2 +9 x+ 3 x √√ - 3 x + 3 = ± 17 √ x = - 3 ± 17 √

7
+ 8 x 2 + 6x = 8 (x + 3) 2 = 17 + 9 +3x x2x2 +9 x+ 3 x √√ x + 3 = ± 17 √ + 20 x 2 = 20 x = ± 20 x = ± 2 5 √ √√ 20 2 10 2 5 √

8
+ 20 x 2 = 20 x = ± 20 x = ± 2 5 √ √√ 20 2 10 2 5 √ √√ x – 5 = 9 x – 5 = - 9 + 5 x = 14 x = - 4

Similar presentations

© 2024 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google